Mathematical Model Derivation of Protean In-Wheel-Motor Used in EV Applications - Jneid, Mahmoud Said; Harth, Peter (Cognitive Sustainability, 2025)
A Protean in-wheel-motor (IWM) is a special type of permanent magnet synchronous motor developed by Protean Electric for direct drive electric vehicle applications. The Protean IWM features a high fault-tolerance substantial for EV applications by dividing the stator into eight independent sub-motors. Each sub-motor features a balanced three-phase system with a spanning of 45o/360o mechanical/electrical on the stator periphery. In total, there are 8 × 3 = 24 phases on the stator distributed with a displacement between any two subsequent phases of 15o/120o mechanical/electrical. In this paper, the mathematical model of a Protean motor in a synchronous rotor frame (d-q) is derived based on a set of Park transforms corresponding to each sub-motor spatial and electrical distribution. The set of Park transforms is then adapted into one generalised Park transform that can be applied to any sub-motor by introducing an angle representing the beginning of each sub-motor.